Measuring and enhancing elective service performance in NHS operating theatres: an overview. - Mayer, E; Faiz, O; Athanasiou, T; Vincent, C (2008)
• The use of overall theatre utilization rates may be misleading when trying to identify underlying operating session inefficiencies • Future, more accurate, measures of efficiency will need to incorporate case-mix adjusted operative output • The optimization of theatre productivity includes methods such as: • Surgeon-specific list volumes • Managing patient flows • Maximizing ambulatory surgery provision • Ring-fencing surgical in-patient elective service provision.